10. Utilization of Narrative Approach in Art Therapy in Children with Behavioural Problems - Hutyrová Miluše (Sciendo, 2016)
The article deals with the possibilities of applying narrative approach in art therapy context and focuses on the situation of problems in social and cultural contexts, the development of alternative stories, and externalization as one of the basic techniques of narrative therapy. Along with looking for dominant, alternative and preferred stories, externalization develops potential for therapeutic and education intervention in individuals of various target groups. The article focuses, in particular, on children exhibiting problematic behaviour and disordered behaviour. The objective is to find the points interconnecting narrative therapy and art therapy in the creative potential and artistic anchorage, which, along with expression, embody a challenge of new opportunities to find new ways, methods and approaches.